High-strength galvanized steel sheet and method for producing same, and member and method for producing same

By setting a hot-dip galvanized layer on the high-strength galvanized steel plate and controlling its composition and microstructure, the machiningability and endurance of the high-strength steel plate in the processing of automobile parts is solved, and yield strength of more than 1000MPa and excellent machining, collision endurance and crack resistance are achieved.

CN119654436APending Publication Date: 2025-03-18JFE STEEL CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380060106.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-29
Filing Date
2023-07-25
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art is difficult to process high-strength galvanized steel plates with a yield strength of 1000 MPa or more into automotive parts, while maintaining good endurance and crack resistance during collisions.

Method used

By setting a hot-dip galvanized layer on the steel plate and controlling the composition and microstructure of the steel plate, the yield strength reaches more than 1000MPa, while optimizing processability, collision endurance and crack resistance. Specific methods include steps such as hot rolling, cold rolling, heating treatment, cooling treatment and galvanizing treatment.

Benefits of technology

It realizes good machining properties, excellent collision endurance and excellent crack-resistance of high-strength galvanized steel plate, and is suitable for the manufacturing of automotive parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119654436A_ABST
    Figure CN119654436A_ABST
Patent Text Reader

Abstract

Provided is a high-strength galvanized steel sheet having a yield strength of 1000 MPa or more and excellent workability, impact resistance, and crack resistance. The amount of diffusible hydrogen in the steel of the steel sheet is 0.60 ppm by mass or less. The steel sheet has a component composition containing, in mass%, 0.150 to 0.450% of C, 0.50 to 3.00% of Si, 1.50 to 4.00% of Mn, 0.100% or less of P, 0.0200% or less of S, 0.100% or less of Al, 0.0100% or less of O, and 0.0100% or less of N, with the remainder being Fe and unavoidable impurities. In the microstructure of the steel sheet, the total area ratio of tempered martensite and bainite is 55-95%, the area ratio of retained austenite is 5-30%, and the abundance ratio (X / Y) of a structure X having a nanohardness of 7.0 GPa or more and a structure Y having a nanohardness of 6.5 GPa or less is 0.5-2.5.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a high-strength galvanized steel sheet having a yield strength (YS) of 1000 MPa or more, a method for producing the same, and a component and a method for producing the same. Background Art

[0002] In recent years, for example, in the automobile industry, there has been a demand for improving the fuel efficiency of automobiles in order to reduce carbon dioxide (CO 2 ) emissions from the viewpoint of protecting the global environment.

[0003] In order to improve the fuel efficiency of automobiles, it is effective to seek to reduce the weight of the vehicle body, but in this case, it is necessary to seek to reduce the weight of the vehicle body while maintaining the strength of the vehicle body. If the steel plates that become automobile parts can be made stronger and the structure of the vehicle body can be simplified to reduce the number of parts, the weight of the vehicle body can be reduced.

[0004] For example, Patent Document 1 discloses a high-strength galvanized steel sheet and also discloses a high-strength galvanized steel sheet having a yield strength of 1000 MPa or more.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2017 / 164346 Summary of the invention

[0008] Problems to be solved by the invention

[0009] In order to form a high-strength galvanized steel sheet having a yield strength of 1000 MPa or more into an automobile part, good workability is required.

[0010] Furthermore, steel sheets used as automobile parts are also required to have excellent resistance during collision (hereinafter referred to as "collision resistance") and to suppress the progress of cracks caused by external forces during collision (excellent crack arrestability).

[0011] Therefore, an object of the present invention is to provide a high-strength galvanized steel sheet having a yield strength of 1000 MPa or more and excellent workability, impact resistance and crack arrestability.

[0012] Methods used to solve problems

[0013] The present inventors have found that the above-mentioned object can be achieved by adopting the following configuration, thereby completing the present invention.

[0014] That is, the present invention provides the following [1] to [5].

[0015] [1] A high-strength galvanized steel sheet comprising a steel sheet and a hot-dip galvanized layer provided on at least one surface of the steel sheet, wherein the yield strength of the high-strength galvanized steel sheet is 1000 MPa or more, the amount of diffusible hydrogen in the steel of the steel sheet is 0.60 mass ppm or less, and the steel sheet has a component composition and a microstructure, wherein the component composition contains, in mass %, C: 0.150-0.450%, Si: 0.50-3.00%, and Mn: 1.50-4.00%. , P: less than 0.100%, S: less than 0.0200%, Al: less than 0.100%, O: less than 0.0100% and N: less than 0.0100%, the balance consisting of Fe and inevitable impurities, in the above microstructure, the total area ratio of tempered martensite and bainite is 55 to 95%, the area ratio of retained austenite is 5 to 30%, and the existence ratio X / Y of structure X with nanohardness of more than 7.0 GPa and structure Y with nanohardness of less than 6.5 GPa is 0.5 to 2.5.

[0016] [2] The high-strength galvanized steel sheet according to the above [1], wherein the above-mentioned component composition further contains, in terms of mass %, at least one element selected from the group consisting of B: less than 0.0100%, Ti: less than 0.200%, Nb: less than 0.200%, V: less than 0.200%, W: less than 0.100%, Mo: less than 1.000%, Cr: less than 1.000%, Sb: less than 0.200%, Sn: less than 0.200%, Zr: less than 0.1000%, Te: less than 0.100%, Cu: less than 1.000%, Ni: less than 1.000%, Ca: less than 0.0100%, Mg: less than 0.0100%, REM: less than 0.0100%, Co: less than 0.010%, Ta: less than 0.10%, Hf: less than 0.10% and Bi: less than 0.200%.

[0017] [3] A method for manufacturing a high-strength galvanized steel sheet, which is a method for manufacturing the high-strength galvanized steel sheet described in [1] or [2] above, wherein a steel billet having the component composition described in [1] or [2] above is hot rolled to obtain a hot-rolled steel sheet, the hot-rolled steel sheet is cold rolled to obtain a cold-rolled steel sheet, the cold-rolled steel sheet is sequentially subjected to a heating treatment, a first cooling, a second cooling and a galvanizing treatment to obtain a galvanized steel sheet, the galvanized steel sheet is sequentially subjected to a third cooling, a reheating treatment and a fourth cooling, in the heating treatment, the cold-rolled steel sheet is heated at a heating temperature T1 of 800 to 950°C, and in the first cooling, the cold-rolled steel sheet is cooled from the heating temperature T1 to ( In the above-mentioned second cooling, the above-mentioned cold-rolled steel sheet is cooled, and the average cooling rate v2 in the temperature range T3 above the Ms point and below (Ms point + 100) ° C is 0.1-5.0 ° C / s, in the above-mentioned third cooling, the above-mentioned galvanized steel sheet is cooled to a cooling stop temperature T4 of 50-350 ° C, and bending-bending recovery is performed more than once in the middle, in the above-mentioned reheating treatment, the above-mentioned galvanized steel sheet is reheated to a reheating temperature T5 below 500 ° C, and re-cooled without being maintained at the above-mentioned reheating temperature T5, and in the above-mentioned fourth cooling, the above-mentioned galvanized steel sheet is maintained at a temperature T6 lower than the above-mentioned reheating temperature T5 for 1-200s.

[0018] [4] A member made of the high-strength galvanized steel sheet according to [1] or [2] above.

[0019] [5] A method for manufacturing a component, wherein the component is obtained by subjecting the high-strength galvanized steel sheet described in [1] or [2] above to at least one of a forming process and a joining process.

[0020] Effects of the Invention

[0021] According to the present invention, it is possible to provide a high-strength galvanized steel sheet having a yield strength of 1000 MPa or more and excellent in workability, impact resistance and crack arrestability. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a diagram showing an example of heat treatment.

[0023] Figure 2A is a cross-sectional view showing a cap member.

[0024] Figure 2B : is a schematic diagram showing a cap member provided for a three-point bending test. DETAILED DESCRIPTION

[0025] [High-strength galvanized steel sheet]

[0026] The high-strength galvanized steel sheet according to the present embodiment (hereinafter also referred to as "the present high-strength galvanized steel sheet") includes a steel sheet and a hot-dip galvanized layer.

[0027] The steel sheet included in the high-strength galvanized steel sheet has a component composition and a microstructure described below, and satisfies the amount of diffusible hydrogen in steel described below.

[0028] High strength means that the yield strength (YS) is 1000 MPa or more.

[0029] The high-strength galvanized steel sheet has a yield strength of 1000 MPa or more and is excellent in workability, collision resistance and crack arrestability. Therefore, since it has sufficient strength against collision, it is suitable for use as a component of a transportation vehicle such as an automobile.

[0030] As a method of forming the high-strength galvanized steel sheet, general processing methods such as press working can be used without limitation. As a method of welding the high-strength galvanized steel sheet, general welding methods such as spot welding and arc welding can be used without limitation.

[0031] <Steel Plate>

[0032] First, the steel sheet (base steel sheet) included in the high-strength galvanized steel sheet will be described.

[0033] The thickness of the steel plate is not particularly limited, and is, for example, 0.5 mm or more and 3.0 mm or less.

[0034] 《Ingredients》

[0035] The chemical composition of the steel sheet included in the present high-strength galvanized steel sheet (hereinafter, also referred to as “the present chemical composition” for convenience) will be described.

[0036] Unless otherwise specified, "%" in the present component composition means "mass %".

[0037] (C: 0.150~0.450%)

[0038] C generates martensite and increases the strength of the steel sheet. When the amount of C is too small, the total area ratio of tempered martensite and bainite decreases, so the collision resistance and yield strength decrease. Therefore, the amount of C is 0.150% or more, preferably 0.180% or more, and more preferably 0.200% or more.

[0039] On the other hand, when the amount of C is too much, the nanohardness of the structure X with a crack starting point of 7.0 GPa or more increases, so the elongation (E1) and hole expansion rate (λ) as indicators of processability decrease. Therefore, the amount of C is 0.450% or less, preferably 0.430% or less, and more preferably 0.400% or less.

[0040] (Si: 0.50~3.00%)

[0041] Si is an element that inhibits carbide formation during heat treatment and affects the hardness of the structure and the stability of retained austenite. From the perspective of ensuring a structure with appropriate nanohardness and ensuring an appropriate amount of retained austenite, the amount of Si is 0.50% or more, preferably 0.70% or more, and more preferably 0.80% or more.

[0042] On the other hand, when the amount of Si is too large, the carbon concentration in the retained austenite increases excessively, and the area ratio of the retained austenite becomes too high.

[0043] Therefore, the amount of Si is 3.00% or less, preferably 2.60% or less, and more preferably 2.40% or less.

[0044] (Mn: 1.50~4.00%)

[0045] Mn affects the area ratio of tempered martensite and bainite. From the viewpoint of obtaining good impact resistance and a yield strength of 1000 MPa or more, the amount of Mn is 1.50% or more, preferably 1.80% or more, and more preferably 2.00% or more.

[0046] On the other hand, when the amount of Mn is too much, the nanohardness of the structure X with a crack starting point of 7.0 GPa or more increases, so the elongation (E1) and hole expansion rate (λ) as indicators of processability decrease. Therefore, the amount of Mn is 4.00% or less, preferably 3.80% or less, and more preferably 3.50% or less.

[0047] (P: 0.100% or less)

[0048] P segregates at the prior austenite grain boundaries and embrittles the grain boundaries, thereby reducing the ultimate deformation energy of the steel sheet, thereby reducing the elongation (El) and hole expansion ratio (λ) as indicators of workability. Therefore, the P amount is 0.100% or less, preferably 0.030% or less, and more preferably 0.010% or less.

[0049] The lower limit of the amount of P is not particularly limited, but P is a solid solution strengthening element and increases the strength of the steel sheet, so it is preferably 0.001%, more preferably 0.002%, and even more preferably 0.003%.

[0050] (S: 0.0200% or less)

[0051] S combines with Mn to form coarse MnS, which serves as a starting point for cracks, so that the elongation (E1) and the hole expansion ratio (λ) which are indicators of workability decrease.

[0052] Therefore, the amount of S is 0.0200% or less, preferably 0.0100% or less, and more preferably 0.0020% or less.

[0053] The lower limit of the amount of S is not particularly limited, but is preferably 0.0001%, more preferably 0.0002%, and further preferably 0.0003% due to restrictions in production technology.

[0054] (Al: 0.100% or less)

[0055] Al increases the A3 transformation point. As a result, ferrite increases and the area ratio of tempered martensite and bainite decreases. Therefore, the amount of Al is 0.100% or less, preferably 0.080% or less, and more preferably 0.060% or less.

[0056] The lower limit of the amount of Al is not particularly limited, but is, for example, 0.010%, preferably 0.020%, from the viewpoint of suppressing the formation of carbides during heat treatment and promoting the formation of retained austenite.

[0057] (O: 0.0100% or less)

[0058] O forms oxides, which become the starting point of cracks, so the elongation (El) and hole expansion ratio (λ) which are indicators of workability are reduced. Therefore, the amount of O is 0.0100% or less, preferably 0.0050% or less, and more preferably 0.0020% or less.

[0059] (N: 0.0100% or less)

[0060] N combines with Ti to form TiN, which becomes the starting point of cracks, so the elongation (El) and hole expansion rate (λ) which are indicators of workability are reduced. Therefore, the amount of N is 0.0100% or less, preferably 0.0080% or less, and more preferably 0.0060% or less.

[0061] The lower limit of the amount of N is not particularly limited, but is preferably 0.0001%, more preferably 0.0003%, and further preferably 0.0005% due to restrictions in production technology.

[0062] (Other elements)

[0063] The present component composition may further contain, in mass %, at least one element selected from the group consisting of the elements described below.

[0064] ((B: 0.0100% or less))

[0065] B is an element that can improve the hardenability of the steel sheet by segregating at the austenite grain boundary, and it is preferably added because it increases the yield strength of the steel sheet.

[0066] However, when the amount of B is too much, Fe23 (CB) 6, becomes the starting point of cracks, and the elongation (El) and hole expansion rate (λ) which are indicators of workability are reduced. Therefore, the B amount is preferably 0.0100% or less, more preferably 0.0050% or less, further preferably 0.0040% or less, and particularly preferably 0.0030% or less.

[0067] The lower limit of the amount of B is not particularly limited, but from the viewpoint of obtaining the effect of adding B, it is, for example, 0.0005%, preferably 0.0010%.

[0068] ((Ti: 0.200% or less))

[0069] Ti forms fine carbides, nitrides, or carbonitrides during hot rolling or heat treatment, thereby increasing the yield strength of the steel sheet, and therefore, it is preferably added.

[0070] However, when the amount of Ti is too large, the number of coarse nitrides formed by combining with N increases as the starting point of cracks, so the elongation (El) and hole expansion ratio (λ) which are indicators of workability decrease. Therefore, the amount of Ti is preferably 0.200% or less, more preferably 0.100% or less, and further preferably 0.050% or less.

[0071] The lower limit of the amount of Ti is not particularly limited, but from the viewpoint of obtaining the effect of adding Ti, it is, for example, 0.005%, preferably 0.010%.

[0072] ((Nb: 0.200% or less, V: 0.200% or less, W: 0.100% or less))

[0073] Nb, V, and W form fine carbides, nitrides, or carbonitrides during hot rolling or heat treatment, thereby increasing the yield strength of the steel sheet, and therefore, are preferably added.

[0074] However, when these elements are added in excessive amounts, they do not melt when the steel slab is heated but remain as coarse carbides. Coarse carbides become starting points for cracks, and the elongation (El) and hole expansion ratio (λ) which are indicators of workability decrease.

[0075] Therefore, the amount of Nb is preferably 0.200% or less, more preferably 0.100% or less, and still more preferably 0.050% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Nb addition, it is, for example, 0.005%, preferably 0.010%.

[0076] The amount of V is preferably 0.200% or less, more preferably 0.100% or less, and still more preferably 0.050% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of V addition, it is, for example, 0.005%, preferably 0.010%.

[0077] The amount of W is preferably 0.100% or less, more preferably 0.080% or less, and still more preferably 0.050% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of W addition, it is, for example, 0.010%, preferably 0.020%.

[0078] ((Mo: 1.000% or less, Cr: 1.000% or less))

[0079] Mo and Cr are preferably added because they increase the yield strength of the steel sheet by improving the hardenability of the steel sheet. However, when the amount of these elements is too large, hard martensite is excessively generated, and the starting point of cracks increases, so the elongation (El) and hole expansion ratio (λ) which are indicators of workability are reduced.

[0080] Therefore, the amount of Mo is preferably 1.000% or less, more preferably 0.800% or less, and still more preferably 0.500% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Mo addition, it is, for example, 0.010%, preferably 0.020%.

[0081] The Cr content is preferably 1.000% or less, more preferably 0.800% or less, and still more preferably 0.500% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Cr addition, it is, for example, 0.010%, preferably 0.020%.

[0082] ((Sb: 0.200% or less, Sn: 0.200% or less))

[0083] Sb and Sn are preferably added because they suppress decarburization on the surface of the steel sheet and increase the yield strength of the steel sheet. However, when the amount of these elements is too large, the steel becomes brittle and the elongation (El) and hole expansion ratio (λ) which are indicators of workability decrease.

[0084] Therefore, the amount of Sb is preferably 0.200% or less, more preferably 0.080% or less, and still more preferably 0.040% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Sb addition, it is, for example, 0.001%, preferably 0.002%.

[0085] The amount of Sn is preferably 0.200% or less, more preferably 0.080% or less, and still more preferably 0.040% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Sn addition, it is, for example, 0.001%, preferably 0.002%.

[0086] ((Zr: 0.1000% or less, Te: 0.100% or less))

[0087] Zr and Te make the shapes of nitrides and sulfides spheroidal, and improve the elongation (El) and hole expansion ratio (λ) which are indicators of workability, so it is preferable to add them. However, when the amount of these elements is too large, the coarse precipitates remaining due to not being dissolved during the heating of the hot-rolled steel slab increase, and the elongation (El) and hole expansion ratio (λ) which are indicators of workability deteriorate.

[0088] Therefore, the amount of Zr is preferably 0.1000% or less, more preferably 0.0800% or less, and still more preferably 0.0500% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of adding Zr, it is, for example, 0.0050%, preferably 0.0100%.

[0089] The amount of Te is preferably 0.100% or less, more preferably 0.080% or less, and still more preferably 0.050% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of adding Te, it is, for example, 0.005%, preferably 0.010%.

[0090] (Cu: 1.000% or less)

[0091] Cu is preferably added because it increases the yield strength of the steel sheet by improving the hardenability of the steel sheet. However, when the amount of Cu is too much, the elongation (El) and hole expansion ratio (λ) which are indicators of workability deteriorate due to the increase in Cu inclusions.

[0092] Therefore, the amount of Cu is preferably 1.000% or less, more preferably 0.800% or less, and still more preferably 0.500% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Cu addition, it is, for example, 0.010%, preferably 0.020%.

[0093] ((Ni: 1.000% or less))

[0094] Ni is preferably added because it increases the yield strength of the steel sheet by improving the hardenability of the steel sheet. However, when the amount of Ni is too large, the elongation (El) and hole expansion ratio (λ) which are indicators of workability deteriorate due to the increase in hard martensite.

[0095] Therefore, the amount of Ni is preferably 1.000% or less, more preferably 0.800% or less, and still more preferably 0.500% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Ni addition, it is, for example, 0.010%, preferably 0.020%.

[0096] (Ca: 0.0100% or less, Mg: 0.0100% or less, REM: 0.0100% or less))

[0097] Ca, Mg and REM (Rare Earth Metal) spheroidize the shape of precipitates such as sulfides and oxides, and increase the elongation (El) and hole expansion ratio (λ) which are indicators of workability, so it is preferable to add them. However, when the amount of these elements is too large, the coarsened sulfides become the starting point of cracks, and the elongation (El) and hole expansion ratio (λ) which are indicators of workability deteriorate.

[0098] Therefore, the amount of Ca is preferably 0.0100% or less, more preferably 0.0050% or less, and still more preferably 0.0040% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Ca addition, it is, for example, 0.0005%, preferably 0.0010%.

[0099] The amount of Mg is preferably 0.0100% or less, more preferably 0.0050% or less, and still more preferably 0.0040% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Mg addition, it is, for example, 0.0005%, preferably 0.0010%.

[0100] The amount of REM is preferably 0.0100% or less, more preferably 0.0040% or less, and still more preferably 0.0030% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of adding REM, it is, for example, 0.0005%, preferably 0.0010%.

[0101] ((Co: 0.010% or less, Ta: 0.10% or less, Hf: 0.10% or less, Bi: 0.200% or less))

[0102] Co, Ta, Hf and Bi make the shape of the precipitates spheroidal, and improve the elongation (E1) and hole expansion ratio (λ) as indicators of workability, so it is preferably added. However, when the amount of these elements is too much, the coarsened precipitates become the starting point of cracks, and the elongation (E1) and hole expansion ratio (λ) as indicators of workability deteriorate.

[0103] Therefore, the amount of Co is preferably 0.010% or less, more preferably 0.008% or less, and still more preferably 0.007% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Co addition, it is, for example, 0.001%, preferably 0.002%.

[0104] The amount of Ta is preferably 0.10% or less, more preferably 0.08% or less, and still more preferably 0.07% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Ta addition, it is, for example, 0.01%, preferably 0.02%.

[0105] The amount of Hf is preferably 0.10% or less, more preferably 0.08% or less, and still more preferably 0.07% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Hf addition, it is, for example, 0.01%, preferably 0.02%.

[0106] The Bi content is preferably 0.200% or less, more preferably 0.100% or less, and still more preferably 0.080% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of adding REM, it is, for example, 0.001%, preferably 0.005%.

[0107] (margin)

[0108] The balance in this component composition is composed of Fe and inevitable impurities.

[0109] Microstructure

[0110] Next, the microstructure of the steel sheet included in the present high-strength galvanized steel sheet (hereinafter, also referred to as “the present microstructure” for convenience) will be described.

[0111] In order to obtain the effects of the present invention, it is not sufficient to satisfy only the above-mentioned present component composition, and it is also necessary to satisfy the present microstructure described below.

[0112] Hereinafter, the area ratio refers to the area ratio relative to the entire microstructure. The area ratio of each structure is obtained by the method described in the Examples described below.

[0113] (Total area ratio of tempered martensite and bainite: 55-95%)

[0114] From the viewpoint of stably ensuring good impact resistance and yield strength, the total area ratio of tempered martensite and bainite is 55% or more, preferably 58% or more, and more preferably 60% or more.

[0115] On the other hand, when the total area ratio of tempered martensite and bainite is too high, the number of structures X having a nanohardness of 7.0 GPa or more increases, and the existence ratio (X / Y) becomes too large.

[0116] Therefore, the total area ratio is 95% or less, preferably 92% or less, and more preferably 88% or less.

[0117] (Area ratio of retained austenite: 5-30%)

[0118] Retained austenite improves the ductility of the steel sheet. Therefore, the area ratio of retained austenite is 5% or more, preferably 6% or more, and more preferably 8% or more.

[0119] On the other hand, when the area ratio of retained austenite is too high, the retained austenite that transforms into martensite increases under repeated stress loading, the number of crack starting points increases, and the elongation (El) and hole expansion ratio (λ) that are indicators of workability deteriorate.

[0120] Therefore, the area ratio of retained austenite is 30% or less, preferably 25% or less, and more preferably 20% or less.

[0121] (Existence ratio X / Y: 0.5 to 2.5)

[0122] The structure X having a nanohardness of 7.0 GPa or more is fine and hard, and improves the crack arrestability by inhibiting the progress of cracks generated by external force during collision.

[0123] On the other hand, since the structure Y having a nanohardness of 6.5 GPa or less has high toughness, the elongation (El) and hole expansion ratio (λ) which are indicators of workability are improved.

[0124] By appropriately controlling the abundance ratio (X / Y) of the structure X to the structure Y, both the workability and the crack arrestability can be improved.

[0125] From the perspective of excellent crack arrestability, the presence ratio (X / Y) is 0.5 or more, preferably 0.8 or more, and more preferably 1.0 or more.

[0126] On the other hand, when the existence ratio (X / Y) of structure X to structure Y is too large, the structure X having a nanohardness of 7.0 GPa or more becomes the starting point of cracks, and the elongation (El) and hole expansion ratio (λ) as indicators of processability deteriorate. Therefore, the existence ratio (X / Y) is 2.5 or less, preferably 2.3 or less, and more preferably 2.0 or less.

[0127] Nanohardness is hardness measured using a nanoindentation method, and is specifically determined by the method described in Examples described below.

[0128] The plastic deformation resistance in a local region of a tissue at a submicron level cannot be evaluated using hardness other than nanohardness (eg, Vickers hardness).

[0129] (Residual Organization)

[0130] In this microstructure, as a structure (remainder structure) other than tempered martensite, bainite and retained austenite, for example, fresh martensite; pearlite; ferrite; iron-based carbonitrides; alloy carbonitrides; inclusions such as MnS and Al2O3; and other well-known structures may be included.

[0131] The area ratio of the surplus structure is preferably 10% or less, more preferably 8% or less, and further preferably 5% or less. When the area ratio of the surplus structure is within this range, the effect of the present invention is not impaired.

[0132] 《Diffusible hydrogen content in steel: 0.60 mass ppm or less》

[0133] When the amount of diffusible hydrogen in steel is too high, delayed fracture occurs, elongation (El) and hole expansion ratio (λ) as indicators of workability deteriorate, and collision resistance decreases. Therefore, the amount of diffusible hydrogen in steel is 0.60 mass ppm or less, preferably 0.50 mass ppm or less, and more preferably 0.40 mass ppm or less.

[0134] The amount of diffusible hydrogen in the steel is determined by the method described in the examples described later.

[0135] <Hot-dip galvanizing layer>

[0136] From the viewpoint of improving corrosion resistance and the like, the high-strength galvanized steel sheet includes a hot-dip galvanizing layer on at least one surface of the steel sheet.

[0137] The hot-dip galvanized layer may be an alloyed hot-dip galvanized layer.

[0138] The hot-dip galvanized layer is formed by galvanizing.

[0139] [Method for producing high-strength galvanized steel sheet]

[0140] Next, a method for producing a high-strength galvanized steel sheet according to the present embodiment (hereinafter referred to as "the present production method") will be described. The present production method is also a method for producing the above-mentioned high-strength galvanized steel sheet.

[0141] Unless otherwise specified, the temperature when heating or cooling the steel billet, steel plate, etc. shown below refers to the surface temperature of the steel billet, steel plate, etc.

[0142] The method for producing molten steel to become a steel billet (steel raw material) is not particularly limited, and a known method using a converter, an electric furnace, etc. can be adopted. Preferably, the steel billet is obtained from the molten steel by a continuous casting method. The steel billet can also be obtained by other methods such as an ingot casting-blowing rolling method and a thin slab continuous casting method.

[0143] <Hot rolling>

[0144] In the present production method, first, a steel slab having the above-mentioned present component composition is hot-rolled to obtain a hot-rolled steel sheet.

[0145] When hot rolling is performed, the steel slab may be reheated in a heating furnace before rolling. When the steel slab is kept at a temperature higher than a predetermined temperature, direct rolling may be performed without heating the steel slab.

[0146] In hot rolling, the steel slab is subjected to rough rolling and finish rolling.

[0147] It is preferred that the steel slab be heated before rough rolling to melt the carbides in the steel slab.

[0148] From the viewpoint of dissolving carbides or preventing an increase in rolling load, the temperature at which the billet is heated (billet heating temperature) is preferably 1100° C. or higher, more preferably 1150° C. or higher.

[0149] On the other hand, from the viewpoint of preventing an increase in scale loss, the slab heating temperature is preferably 1300° C. or lower, more preferably 1280° C. or lower.

[0150] As described above, when the steel slab before rough rolling is maintained at a temperature equal to or higher than a predetermined temperature and carbides in the steel slab are melted, heating of the steel slab before rough rolling can be omitted.

[0151] The conditions for rough rolling and finish rolling are not particularly limited. For example, the finish rolling end temperature is preferably 700 to 1100°C, more preferably 800 to 1000°C.

[0152] <Cold Rolling>

[0153] Next, the hot-rolled steel sheet is cold-rolled to obtain a cold-rolled steel sheet.

[0154] The rolling reduction rate of cold rolling is preferably 30% or more, more preferably 35% or more. The upper limit is not particularly limited, but is, for example, 70% or less, preferably 65% ​​or less.

[0155] <Heat treatment (including galvanizing)>

[0156] Next, the cold-rolled steel sheet obtained by cold rolling is subjected to heat treatment.

[0157] Figure 1 This is a diagram showing an example of heat treatment.

[0158] In the heat treatment, in short, the cold-rolled steel sheet is subjected to heating treatment, first cooling, second cooling and galvanizing treatment in sequence to obtain a galvanized steel sheet. Next, the galvanized steel sheet is subjected to third cooling, reheating treatment and fourth cooling in sequence.

[0159] Figure 1 This is an example where the temperature T2 is (Ms point + 100)°C.

[0160] The galvanized steel sheet that has undergone the fourth cooling is equivalent to the above-mentioned high-strength galvanized steel sheet.

[0161] 《Heat treatment》

[0162] First, the cold-rolled steel sheet is heated at a heating temperature T1.

[0163] (Heating temperature T1: 800~950℃)

[0164] When the heating temperature T1 is too low, heating is performed in a dual phase region of ferrite and austenite. Therefore, the final microstructure contains ferrite, and the total area ratio of tempered martensite and bainite decreases.

[0165] Therefore, the heating temperature T1 is 800°C or higher, preferably 820°C or higher, and more preferably 850°C or higher.

[0166] On the other hand, when the heating temperature T1 is too high, the amount of hydrogen intruding into the steel increases due to the increase in the hydrogen partial pressure, so that the amount of diffusible hydrogen in the steel increases.

[0167] In addition, the total area ratio of tempered martensite and bainite increases, and the abundance ratio (X / Y) of structure X to structure Y becomes too large.

[0168] Therefore, the heating temperature T1 is 950°C or lower, preferably 930°C or lower, and more preferably 900°C or lower.

[0169] The time for which the cold-rolled steel sheet is kept at the heating temperature T1 (heating time t1) is not particularly limited, and is, for example, 10 s or longer, preferably 50 s or longer, and more preferably 80 s or longer.

[0170] On the other hand, the heating time t1 is, for example, 500 s or less, preferably 300 s or less, and more preferably 200 s or less.

[0171] The First Cooling

[0172] Next, the first cooling is performed.

[0173] Specifically, the cold-rolled steel sheet heated at the heating temperature T1 is cooled to a temperature T2 of (Ms point + 100)°C or higher and (Ms point + 600)°C or lower.

[0174] Ms point (unit: °C) is obtained by the following formula (1).

[0175] Ms=550-350×[C]-40×[Mn]-35×[V]-20×[Cr]-17×[Ni]-10×[Cu]-10×[Mo]-5×[W]+15×[Co]+30×[Al]…(1)

[0176] In the above formula (1), [M] is the content (unit: mass %) of the element M in the above component composition (present component composition).

[0177] (Average cooling rate v1: 10℃ / s or more)

[0178] In the first cooling, if the average cooling rate v1 from the heating temperature T1 to the temperature T2 is too low, ferrite transformation occurs during cooling, and the total area ratio of tempered martensite and bainite decreases.

[0179] Therefore, the average cooling rate v1 is 10° C. / s or more, preferably 11° C. / s or more, and more preferably 13° C. / s or more.

[0180] The upper limit of the average cooling rate v1 is not particularly limited, but is, for example, 40° C. / s, preferably 35° C. / s, and more preferably 30° C. / s.

[0181] The Second Cooling

[0182] Next, a second cooling is performed.

[0183] Specifically, the cold-rolled steel sheet cooled to the temperature T2 is cooled to at least the Ms point before being subjected to the galvanizing treatment described later.

[0184] (Average cooling rate v2: 0.1~5.0℃ / s)

[0185] In the second cooling, hydrogen introduced into the cold-rolled steel sheet by the above-mentioned heating treatment is desorbed.

[0186] At this time, if the cold-rolled steel sheet is slowly cooled in the temperature range T3 of not less than the Ms point and not more than (Ms point + 100)°C, bainite transformation occurs, and austenite with high hydrogen solubility decreases, thereby reducing the amount of diffusible hydrogen in the steel.

[0187] Therefore, the average cooling rate v2 in the temperature range T3 is 0.1° C. / s or more, preferably 0.2° C. / s or more, and more preferably 0.3° C. / s or more.

[0188] On the other hand, when the average cooling rate v2 in the temperature range T3 is too high, the total area ratio of tempered martensite and bainite decreases.

[0189] Therefore, the average cooling rate v2 is 5.0° C. / s or less, preferably 4.5° C. / s or less, and more preferably 4.0° C. / s or less.

[0190] 《Galvanizing treatment》

[0191] Next, the cold-rolled steel sheet cooled to at least the Ms point is subjected to galvanizing treatment, thereby obtaining a galvanized steel sheet.

[0192] The galvanizing treatment is preferably hot-dip galvanizing treatment or alloy hot-dip galvanizing treatment.

[0193] A hot-dip galvanizing layer is formed by performing hot-dip galvanizing.

[0194] When hot-dip galvanizing is performed, for example, the steel sheet is immersed in a zinc bath at a bath temperature of 440 to 500° C. Then, the coating weight is preferably adjusted by gas wiping or the like.

[0195] The zinc bath preferably has a composition in which the Al content is 0.10 to 0.23% by mass and the balance is Zn and unavoidable impurities.

[0196] A galvannealed layer is formed by performing a galvannealed treatment.

[0197] When performing alloying hot-dip galvannealing, when the alloying temperature is too low, the Zn-Fe alloying rate sometimes becomes too slow, and alloying becomes significantly difficult. On the other hand, when the alloying temperature is too high, the untransformed austenite sometimes transforms into pearlite. Therefore, the alloying temperature is preferably 450 to 600°C, more preferably 470 to 550°C, and further preferably 470 to 530°C.

[0198] The coating weight of the zinc coating layer in hot-dip galvanized steel sheets (GI) and alloyed hot-dip galvanized steel sheets (GA) is preferably 20 to 80 g / m per side. 2 (Both sides plated).

[0199] The Third Cooling

[0200] Next, the third cooling is performed.

[0201] Specifically, the galvanized steel sheet is cooled to the cooling stop temperature T4, and bending-bending recovery is performed one or more times during the cooling.

[0202] (Cooling stop temperature T4: 50~350℃)

[0203] When the cooling stop temperature T4 is too low, the total area ratio of tempered martensite and bainite increases, and the abundance ratio (X / Y) of the structure X to the structure Y becomes too large.

[0204] Therefore, the cooling stop temperature T4 is 50°C or higher, preferably 100°C or higher, and more preferably 150°C or higher.

[0205] On the other hand, when the cooling stop temperature T4 is too high, the total area ratio of tempered martensite and bainite decreases. In addition, the structure Y with a nanohardness of 6.5 GPa or less increases, and the abundance ratio (X / Y) of the structure X to the structure Y becomes too small.

[0206] Therefore, the cooling stop temperature T4 is 350°C or lower, preferably 320°C or lower, and more preferably 300°C or lower.

[0207] (Bending-bending recovery times: more than 1 time)

[0208] Bending and bending recovery are performed while the galvanized steel sheet is cooled to the cooling stop temperature T4, thereby introducing dislocations into the cold-rolled steel sheet constituting the galvanized steel sheet. The introduced dislocations become trapping sites for diffusible hydrogen in the steel, and can reduce the amount of diffusible hydrogen in the steel.

[0209] Therefore, the number of bend-bend recovery is 1 time or more, preferably 2 times or more, and more preferably 3 times or more.

[0210] On the other hand, the upper limit of the number of bend-bend recovery times is not particularly limited, and is, for example, 10 times, preferably 8 times, and more preferably 6 times.

[0211] Reheating treatment

[0212] Next, a reheating treatment is performed.

[0213] Specifically, the galvanized steel sheet subjected to bending-bend recovery one or more times is reheated to the reheating temperature T5, and is recooled without being held at the reheating temperature T5.

[0214] (Reheating temperature T5)

[0215] The reheating temperature T5 is 500°C or lower, preferably 450°C or lower, and more preferably 400°C or lower.

[0216] Therefore, in the cold-rolled steel sheet constituting the galvanized steel sheet, bainite transformation proceeds and retained austenite is likely to remain.

[0217] The Fourth Cooling

[0218] Next, the fourth cooling is performed.

[0219] Specifically, the galvanized steel sheet after being re-cooled without being held at the reheating temperature T5 is held at the temperature T6.

[0220] (Temperature T6: lower than reheating temperature T5)

[0221] By maintaining the galvanized steel sheet at a temperature T6 lower than the reheating temperature T5, the cold-rolled steel sheet constituting the galvanized steel sheet is not excessively tempered, and the distribution of the structure X and the structure Y can be well controlled.

[0222] When the temperature T6 is equal to or higher than the reheating temperature T5, the structure Y having a nanohardness of 6.5 GPa or less increases, and the abundance ratio (X / Y) of the structure X to the structure Y becomes too small.

[0223] (Holding time t6 at temperature T6: 1 to 200 s)

[0224] When the galvanized steel sheet is kept at temperature T6 for too short a time (holding time t6), carbon in each structure exists in a solid solution state in the microstructure of the cold-rolled steel sheet constituting the galvanized steel sheet. As a result, the structure X having a nanohardness of 7.0 GPa or more increases, and the existence ratio (X / Y) of the structure X to the structure Y becomes too large.

[0225] Therefore, the holding time t6 is 1 s or longer, preferably 10 s or longer, and more preferably 20 s or longer.

[0226] On the other hand, when the holding time t6 is too long, in the microstructure of the cold-rolled steel sheet constituting the galvanized steel sheet, carbon in each structure exists in the form of carbide. As a result, the structure Y with a nanohardness of less than 6.5 GPa increases, and the existence ratio (X / Y) of the structure X to the structure Y becomes too small.

[0227] Therefore, the holding time t6 is 200 s or less, preferably 180 s or less, and more preferably 150 s or less.

[0228] In the present manufacturing method, for example, the holding temperature such as the heating temperature and the reheating temperature may not be constant as long as they are within the above temperature range. The cooling rate may also be changed during cooling as long as it is within the above speed range. As long as the above temperature range and other conditions are met, the heat treatment may be performed with any equipment.

[0229] [member]

[0230] Next, the components of the present embodiment (hereinafter also referred to as “present components”) will be described.

[0231] This component is a component at least partly formed using the above-mentioned high-strength galvanized steel sheet, for example, a component formed by forming the high-strength galvanized steel sheet into a target shape by processing (press processing, etc.).

[0232] The present member is preferably a member for automobile parts. It should be noted that the member for automobile parts may include a steel sheet other than the present high-strength galvanized steel sheet as a raw material.

[0233] As described above, the high-strength galvanized steel sheet has a yield strength of more than 1000 MPa and is excellent in processability, collision resistance and crack arrest. Therefore, the member has excellent processability, collision resistance and crack arrest, and can contribute to the lightweight of the vehicle body. Therefore, among automobile parts, it is particularly suitable as all members used in the frame structure parts of the automobile or the reinforcement parts of the automobile.

[0234] [Method of manufacturing component]

[0235] Next, a method for producing the present member will be described.

[0236] The present member is obtained, for example, by subjecting the present high-strength galvanized steel sheet to at least one of a forming process and a joining process.

[0237] The forming process is not particularly limited, and examples thereof include press working and the like.

[0238] The joining process is not particularly limited, and examples thereof include general welding such as spot welding and arc welding, and riveting using rivets or the like.

[0239] Example

[0240] Hereinafter, the present invention will be described in detail with reference to Examples, but the present invention is not limited to the Examples described below.

[0241] <Manufacturing of Steel Plate>

[0242] Molten steel having the composition shown in Table 1 below, with the balance being Fe and inevitable impurities, was produced by a converter, and steel slabs were obtained by continuous casting. The underlined parts in Table 1 below are outside the scope of the present invention (the same applies to Tables 2 and 3 described below).

[0243] The obtained steel slab was hot rolled under the conditions shown in the following Table 2 to obtain a hot rolled steel sheet. Specifically, the steel slab was heated to 1250°C, rough rolled, and then finish rolled at a finish rolling end temperature of 900°C.

[0244] The obtained hot-rolled steel sheets were cold-rolled at the rolling ratios shown in Table 2 below, thereby obtaining cold-rolled steel sheets (sheet thickness: 1.2 mm).

[0245] The obtained cold-rolled steel sheet was subjected to heating treatment, first cooling, second cooling and galvanizing treatment under the conditions shown in Table 2 below to obtain a galvanized steel sheet.

[0246] In addition, in the heat treatment, the holding time at the heating temperature T1 (heating time t1) was set to 120 seconds.

[0247] In the galvanizing treatment, both surfaces of the cold-rolled steel sheet are subjected to hot-dip galvanizing treatment or alloyed hot-dip galvanizing treatment to obtain a hot-dip galvanized steel sheet (GI) or an alloyed hot-dip galvanized steel sheet (GA).

[0248] As the hot-dip galvanizing bath, a zinc bath containing Al: 0.20 mass % and the balance consisting of Zn and inevitable impurities is used when manufacturing GI, and a zinc bath containing Al: 0.14 mass % and the balance consisting of Zn and inevitable impurities is used when manufacturing GA.

[0249] The bath temperature was set to 470° C. in the case of producing both GI and GA.

[0250] The coating weight is set to 45 to 72 g / m per side when manufacturing GI. 2 When manufacturing GA, set it to 45g / m per single side. 2 .

[0251] In the case of producing GA, the alloying temperature was set to 530°C.

[0252] The composition of the GI plating layer contains Fe: 0.1-1.0 mass%, Al: 0.2-1.0 mass%, and the balance is Fe and inevitable impurities. The composition of the GA plating layer contains Fe: 7-15 mass%, Al: 0.1-1.0 mass%, and the balance is Fe and inevitable impurities.

[0253] Next, the obtained galvanized steel sheet (GI or GA) was subjected to third cooling, reheating treatment, and fourth cooling under the conditions shown in Table 2 below.

[0254] Hereinafter, the galvanized steel sheet (GI or GA) subjected to such a heat treatment (specifically, subjected to the fourth cooling) will also be simply referred to as a "steel sheet".

[0255] <Observation of Microstructure>

[0256] The microstructure of the obtained steel plate was observed as follows. The results are shown in the following Table 3. In addition, in the following Table 3, martensite is expressed as "M", bainite is expressed as "B", and austenite is expressed as "γ".

[0257] 《Total area ratio of tempered martensite and bainite》

[0258] The obtained steel plate was polished so that the cross section (L cross section) at the 1 / 4 position of the plate thickness and parallel to the rolling direction was used as the observation surface. The observation surface was corroded with 1 vol % nitric acid solution and observed with a scanning electron microscope (SEM) at a magnification of 3000 times.

[0259] The observation surface was observed in 10 fields to obtain a SEM image, and the obtained SEM image was analyzed to determine the total area ratio (unit: %) of tempered martensite and bainite.

[0260] More specifically, dark gray portions in the obtained SEM images were determined to be tempered martensite and bainite, and their area ratios (average area ratios of 10 fields of view) were determined. In the analysis of the SEM images, Image-Pro manufactured by MediaCybernetics was used as analysis software.

[0261] 《Area ratio of retained austenite》

[0262] For the observed surface of the obtained steel plate (L cross section at a position of 1 / 4 of the plate thickness), an X-ray diffraction (XRD) apparatus was used with CoKα as an X-ray source to determine the diffraction intensity of the crystal plane described below.

[0263] Specifically, the ratio of the diffraction intensity of each of the (200), (220) and (311) planes of fcc iron (austenite) to the diffraction intensity of each of the (200), (211) and (220) planes of bcc iron is obtained, and the value obtained by averaging the obtained 9 ratios is taken as the volume fraction of retained austenite.

[0264] The calculated volume fraction was regarded as the area fraction of retained austenite (unit: %).

[0265] 《Determination of Nanohardness》

[0266] The obtained steel plate was polished so that the cross section (L cross section) at the position of 1 / 4 of the plate thickness and parallel to the rolling direction was the observation surface. The observation surface was mirror-polished using diamond paste, and then buff-polished using colloidal silica.

[0267] The nanohardness of the observation surface was measured at 225 points using a nanoindentation device equipped with a Bosch indenter.

[0268] As measurement conditions, the loading speed and the unloading speed were set to 50 μN / s, the maximum load was set to 500 μN, the data collection interval was set to 5 ms, and the distance between indentations was set to 2 μm or more.

[0269] Among the 225 measurement points, measurement points with nanohardness of 7.0 GPa or more were defined as structure X, and measurement points with nanohardness of 6.5 GPa or less were defined as structure Y. The ratio of the number of measurement points was determined as the abundance ratio of structure X to structure Y (X / Y).

[0270] <Determination of Diffusible Hydrogen Amount in Steel>

[0271] After removing the galvanized layer from the obtained steel plate using a router (precision grinder), a test piece with a length of 30 mm and a width of 5 mm was cut. The cut test piece was used to measure the amount of diffusible hydrogen in the steel by the temperature rise desorption analysis method. The heating rate was set to 200°C / hour. The cumulative value of the amount of hydrogen detected in the temperature range from room temperature (25°C) to below 210°C was taken as the amount of diffusible hydrogen in the steel (unit: mass ppm).

[0272] The results are shown in the following Table 3. The amount of diffusible hydrogen in the steel is preferably 0.60 mass ppm or less.

[0273] <Evaluation>

[0274] The obtained steel sheets were evaluated by the following methods. The results are shown in Table 3 below.

[0275] Tensile test

[0276] From the obtained steel plate, a No. 5 test piece described in JIS Z 2241 was cut out with the direction at 90° to the rolling direction as the longitudinal direction (tensile direction). Using the cut test piece, a tensile test according to JIS Z 2241 was performed 5 times, and the yield strength (YS) and elongation (El) were calculated from the average values ​​of the 5 times.

[0277] When YS is 1000 MPa or more, it can be evaluated as high strength.

[0278] When El is 9.0% or more, it can be evaluated that the ductility is good and the workability is excellent.

[0279] Hole expansion test

[0280] In accordance with JIS Z 2256, a hole expansion test was performed on the obtained steel plates.

[0281] Specifically, first, the obtained steel plate was sheared to obtain a test piece of 100 mm × 100 mm in size. A hole with a diameter of 10 mm was punched out of the cut test piece with a clearance of 12.5%. Then, a 75 mm inner diameter die was used to press a conical punch with a vertex angle of 60° into the hole under a state of suppressing a wrinkle resistance of 9 tons (88.26 kN) to measure the hole diameter D at the limit of cracking. f (Unit: mm) The initial pore diameter is defined as D0 (unit: mm), and the pore expansion ratio λ (unit: %) is calculated from the following formula.

[0282] When λ is 20% or more, it can be evaluated that the processability is excellent.

[0283] λ={(D f -D0) / D0}×100

[0284] 《Collision Endurance Evaluation Test》

[0285] A member (hat member) having a hat-shaped cross section was produced using the obtained steel plate, and a three-point bending test was performed to determine the maximum load (unit: kN).

[0286] First, based on Figure 2A , the cap member 1 is described.

[0287] Figure 2A 2 is a cross-sectional view showing the cap member 1 . Figure 2A, the dimensions of the cap member 1 are shown. The cap member 1 is joined to the flat plate 2 by spot welding (nugget diameter: 4.5√t, spot spacing: 35 mm). The flat plate 2 is a cold-rolled steel plate without coating, with a tensile strength (TS) of 590 MPa and a plate thickness t that is the same as that of the cap member 1 (1.2 mm).

[0288] Next, based on Figure 2B , the three-point bending test is explained.

[0289] Figure 2B 1 is a schematic diagram showing the cap member 1 subjected to a three-point bending test. Figure 2B Various dimensions are also shown in FIG. The flat plate 2 joined to the cap member 1 is supported by the support member 3 as a rigid body. In this state, the impactor 4 as a rigid body is moved from above toward the cap member 1 at a speed of 1 m / s. In this way, a three-point bending test is implemented.

[0290] The three-point bending test was performed three times on each steel plate, and the average value of the maximum loads obtained each time was taken as the maximum load of the steel plate.

[0291] In Table 3 below, a maximum load of 40 kN or more is indicated as "◎", a maximum load of 30 kN or more and less than 40 kN is indicated as "○", and a maximum load of less than 30 kN is indicated as "×".

[0292] If it is "◎" or "○", it can be evaluated that the collision resistance is excellent.

[0293] 《Crack arrest evaluation test》

[0294] The obtained steel plate was bent using a 90-degree V-block under the following test conditions to obtain a test piece. The ridgeline of the bending vertex in the obtained test piece was observed at a magnification of 40 times using a digital microscope (RH-2000, manufactured by HIROX Corporation) to measure the length of the crack. In the case of multiple cracks, the total length of the cracks was calculated.

[0295] In Table 3 below, the case where the total length of cracks was 6000 μm or less was indicated as “◎”, the case where the total length of cracks was greater than 6000 μm and less than 12000 μm was indicated as “○”, and the case where the total length of cracks was greater than 12000 μm was indicated as “×”.

[0296] If it is "◎" or "○", it can be evaluated that the crack arrestability is excellent.

[0297] (Test conditions)

[0298] Test method: Roller support, punch press

[0299] Roller diameter: φ30mm

[0300] Punch tip R: 0.4mm

[0301] Distance between rollers: (plate thickness × 2) + 0.5 mm

[0302] Stroke speed: 20mm / min

[0303] Test piece size: 60mm×60mm

[0304] Bending direction: Rolling right angle method

[0305]

[0306]

[0307] [Table 2]

[0308]

[0309]

[0310] [Table 3]

[0311]

[0312]

[0313] <Summary of evaluation results>

[0314] As shown in Tables 1 to 3, the steel plates Nos. 1 to 3, 6 to 8, 10, 15 to 17, 21 to 22, 30, and 33 to 42 all have a yield strength of 1000 MPa or more and are excellent in workability, impact resistance, and crack arrestability.

[0315] On the other hand, the steel sheets of Nos. 4 to 5, 9, 11 to 14, 18 to 20, 23 to 29, and 31 to 32 were insufficient in at least one of the yield strength, workability, impact resistance, and crack arrestability.

Claims

1. A high-strength galvanized steel sheet, comprising a steel sheet and a hot-dip galvanized layer provided on at least one surface of the steel sheet, wherein: The yield strength of the high-strength galvanized steel sheet is above 1000 MPa. The steel plate has a diffusible hydrogen content of 0.60 mass ppm or less. The steel plate has a composition and a microstructure, The composition contains, in mass%, C: 0.150-0.450%, Si: 0.50-3.00%, Mn: 1.50-4.00%, P: 0.100% or less, S: 0.0200% or less, Al: 0.100% or less, O: 0.0100% or less, and N: 0.0100% or less, with the balance being Fe and inevitable impurities. In the microstructure, the total area ratio of tempered martensite and bainite is 55-95%, the area ratio of retained austenite is 5-30%, and the existence ratio X / Y of structure X with nanohardness of 7.0 GPa or more and structure Y with nanohardness of 6.5 GPa or less is 0.5-2.

5.

2. The high-strength galvanized steel sheet according to claim 1, wherein: The composition further comprises, by mass%, B selected from: At least one element selected from the group consisting of Ti: 0.0100% or less, Ti: 0.200% or less, Nb: 0.200% or less, V: 0.200% or less, W: 0.100% or less, Mo: 1.000% or less, Cr: 1.000% or less, Sb: 0.200% or less, Sn: 0.200% or less, Zr: 0.1000% or less, Te: 0.100% or less, Cu: 1.000% or less, Ni: 1.000% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, REM: 0.0100% or less, Co: 0.010% or less, Ta: 0.10% or less, Hf: 0.10% or less, and Bi: 0.200% or less.

3. A method for manufacturing a high-strength galvanized steel sheet, which is a method for manufacturing the high-strength galvanized steel sheet according to claim 1 or 2, wherein: A steel slab having the component composition described in claim 1 or 2 is hot-rolled to obtain a hot-rolled steel sheet. The hot-rolled steel sheet is cold-rolled to obtain a cold-rolled steel sheet. The cold-rolled steel sheet is subjected to a heating treatment, a first cooling treatment, a second cooling treatment and a galvanizing treatment in sequence to obtain a galvanized steel sheet. The galvanized steel sheet is sequentially subjected to a third cooling process, a reheating process and a fourth cooling process. In the heating treatment, the cold-rolled steel sheet is heated at a heating temperature T1 of 800 to 950° C. In the first cooling, the cold-rolled steel sheet is cooled from the heating temperature T1 to a temperature T2 of (Ms point + 100)°C or higher and (Ms point + 600)°C or lower at an average cooling rate v1 of 10°C / s or higher. In the second cooling, the cold-rolled steel sheet is cooled, and an average cooling rate v2 in a temperature range T3 of 0.1 to 5.0°C / s is set within a temperature range T3 of at least Ms point and not more than (Ms point+100)°C. In the third cooling, the galvanized steel sheet is cooled to a cooling stop temperature T4 of 50 to 350° C., and bending-bending recovery is performed one or more times in the middle. In the reheating treatment, the galvanized steel sheet is reheated to a reheating temperature T5 of 500° C. or less, and is recooled without being held at the reheating temperature T5. In the fourth cooling, the galvanized steel sheet is maintained at a temperature T6 lower than the reheating temperature T5 for 1 to 200 seconds.

4. A member formed by using the high-strength galvanized steel sheet according to claim 1 or 2.

5. A method for manufacturing a component, wherein: A member is obtained by subjecting the high-strength galvanized steel sheet according to claim 1 or 2 to at least one of a forming process and a joining process.

Citation Information

Patent Citations

  • High strength steel sheet and high strength galvanized steel sheet

    WO2017164346A1